Jararaca GPIb-binding protein causes thrombocytopenia during Bothrops jararaca envenomation - Marcelo Larami Santoro; Ana Teresa Azevedo Sachetto; Jaqueline Gomes Rosa; Ricardo José Soares Torquato; Débora Andrade-Silva; Dilza Trevisan-Silva; Cynthia Zaccanini de Albuquerque; Solange M. T. Serrano; Vânia Gomes de Moura Mattaraia; Aparecida Sadae Tanaka; Maria Elisa Peichoto (Scientific Reports)
Abstract Inoculation of Bothrops jararaca snake venom (BjV) induces thrombocytopenia in humans and various animal species. Although several BjV toxins acting on hemostasis have been well characterized in vitro, it is not known which one is responsible for inducing thrombocytopenia in vivo. In previous studies, we showed that BjV incubated with metalloproteinase or serine proteinase inhibitors and/or anti-botrocetin antibodies still induced thrombocytopenia in rats and mice. Thus, herein we identified and characterized BjV toxins responsible for inducing thrombocytopenia. Initially, by filtering BjV on ultrafiltration systems, proteins with molecular masses between 30 and 50 kDa were shown to induce thrombocytopenia in mice, but they were not associated with hemorrhagic or coagulating activities. The 50 kDa ultrafiltrate was chromatographed, and two proteins (named fraction D and fraction E) induced thrombocytopenia in mice. However, neither fraction D nor fraction E induced platelet aggregation in platelet-rich plasma or whole blood from humans or mice. By mass spectrometry analysis, fraction E was identified as jararaca glycoprotein Ib (GPIb)-binding protein. Injection of these fractions caused thrombocytopenia in control or Vwf −/− mice, showing that the axis platelet GPIb – von Willebrand factor is not involved in their biological action in vivo. New studies are necessary to understand how these proteins act in vivo.